Vaccination coverage, vaccine hesitancy and factors associated with incomplete vaccination: a household survey conducted with children born between 2017 and 2018 in the inland municipalities of Northeastern Brazil. - Ferreira, Anderson Fuentes (2025)
Adriana Ilha da Silva Universidade Federal do Espírito Santo. Vitória, ES, Brasil. Alberto Novaes Ramos Jr Universidade Federal do Ceará. Departamento de Saúde Comunitária. Fortaleza, CE, Brasil. Ana Paula França Santa Casa de São Paulo. Faculdade de Ciências Médicas. São Paulo, SP, Brasil. Andrea de Nazaré Marvão Oliveira Estado do Amapá. Secretaria de Estado da Saúde. Macapá, AP, Brasil. Antonio Fernando Boing Universidade Federal de Santa Catarina. SC, Brasil. Carla Magda Allan Santos Domingues Organização Pan-Americana da Saúde. Brasília, DF, Brasil. Consuelo Silva de Oliveira Instituto Evandro Chagas. Belém, PA, Brasil. Ethel Leonor Noia Maciel Universidade Federal do Espírito Santo. Vitória, ES, Brasil. Ione Aquemi Guibu Santa Casa de São Paulo. Faculdade de Ciências Médicas. Departamento de Saúde Coletiva. São Paulo, SP, Brasil. Isabelle Ribeiro Barbosa Mirabal Santa Casa de São Paulo. Faculdade de Ciências Médicas. Departamento de Saúde Coletiva. São Paulo, SP, Brasil. Jaqueline Caracas Barbosa Santa Casa de São Paulo. Faculdade de Ciências Médicas. Departamento de Saúde Coletiva. São Paulo, SP, Brasil. Jaqueline Costa Lima Universidade Federal de Mato Grosso. Cuiabá, MT, Brasil. José Cássio de Moraes Santa Casa de São Paulo. Faculdade de Ciências Médicas. São Paulo, SP, Brasil. Karin Regina Luhm Universidade Federal do Paraná. Curitiba, PR, Brasil. Karlla Antonieta Amorim Caetano Universidade Federal de Goiás. Goiânia, GO, Brasil. Luisa Helena de Oliveira Lima Universidade Federal do Piauí, Teresina, PI, Brasil. Maria Bernadete de Cerqueira Antunes Universidade de Pernambuco. Faculdade de Ciências Médicas. Recife, PE, Brasil. Maria da Gloria Teixeira Universidade Federal da Bahia. Instituto de Saúde Coletiva. Salvador, BA, Brasil. Maria Denise de Castro Teixeira Secretaria de Estado da Saúde de Alagoas. Maceió, AL, Brasil. Maria Fernanda de Sousa Oliveira Borges Universidade Federal do Acre. Rio Branco, AC, Brasil. Rejane Christine de Sousa Queiroz Universidade Federal do Maranhão. Departamento de Saúde Pública. São Luís, MA, Brasil. Ricardo Queiroz Gurgel Universidade Federal de Sergipe. Aracaju, SE, Brasil. Rita Barradas Barata Santa Casa de São Paulo. Faculdade de Ciências Médicas. Departamento de Saúde Coletiva. São Paulo, SP, Brasil. Roberta Nogueira Calandrini de Azevedo Prefeitura de Boa Vista. Secretaria Municipal de Saúde. Boa Vista, RR, Brasil. Sandra Maria do Valle Leone de Oliveira Fundação Oswaldo Cruz. Mato Grosso do Sul. Campo Grande, MS, Brasil. Sheila Araújo Teles Universidade Federal de Goiás. Goiânia, GO, Brasil. Silvana Granado Nogueira da Gama Fundação Oswaldo Cruz. Escola Nacional de Saúde Pública Sergio Arouca. Rio de Janeiro, RJ, Brasil. Sotero Serrate Mengue Universidade Federal do Rio Grande do Sul. Porto Alegre, RS, Brasil. Taynãna César Simões Fundação Oswaldo Cruz. Instituto de Pesquisa René Rachou. Belo Horizonte, MG, Brasil. Valdir Nascimento Estado de Rondônia. Secretaria de Desenvolvimento Ambiental. Porto Velho, RO, Brasil. Wildo Navegantes de Araújo Universidade de Brasília. Brasília, DF, Brasil.